Environmental analysis: The applicability of current theory - Lenz, R. T.; Engledow, Jack L. (Strategic Management Journal, 1986)
Abstract It is suggested that senior‐level executives and corporate staff are under mounting pressure to develop better means for assessing organizational environments. This comes at a time when there is little agreement about the concept of environment, relevant perspectives from which it should be viewed, and how to organize for its evaluation. Alternative ‘models’ for environmental analysis are examined, and theoretical issues and their administrative implications are discussed.